Ropivacaine use in transnasal sphenopalatine ganglion block for post dural puncture headache in obstetric patients - case series - Furtado,Inês (2018)
Abstract Purpose Sphenopalatine ganglion block is widely accepted in chronic pain; however it has been underestimated in post dural puncture headache treatment. The ganglion block does not restore normal cerebrospinal fluid dynamics but effectively reduces symptoms associated with resultant hypotension. When correctly applied it may avoid performance of epidural blood patch. The transnasal approach is a simple and minimally invasive technique. In the cases presented, we attempted to perform and report the ganglion block effectiveness and duration, using ropivacaine. Clinical features We present four obstetrics patients with post dural puncture headache, after epidural or combined techniques, with Tuohy needle 18G that underwent a safe and successful sphenopalatine ganglion block. We performed the block 24-48 h after dural puncture, with 4 mL of ropivacaine 0.75% in each nostril. In three cases pain recurred within 12-48 h, although less intense. In one patient a second block was performed with complete relief and without further recurrence. In the other two patients a blood patch was performed without success. All patients were asymptomatic within 7 days. Conclusion The average duration of analgesic effect of the block remains poorly defined. In the cases reported, blocking with ropivacaine was a simple, safe and effective technique, with immediate and sustained pain relief for at least 12-24 h.